2013
DOI: 10.1371/journal.ppat.1003556
|View full text |Cite
|
Sign up to set email alerts
|

Brucella Modulates Secretory Trafficking via Multiple Type IV Secretion Effector Proteins

Abstract: The intracellular pathogenic bacterium Brucella generates a replicative vacuole (rBCV) derived from the endoplasmic reticulum via subversion of the host cell secretory pathway. rBCV biogenesis requires the expression of the Type IV secretion system (T4SS) VirB, which is thought to translocate effector proteins that modulate membrane trafficking along the endocytic and secretory pathways. To date, only a few T4SS substrates have been identified, whose molecular functions remain unknown. Here, we used an in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
192
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(198 citation statements)
references
References 65 publications
4
192
0
2
Order By: Relevance
“…Candidate effectors were shown to target secretory pathway compartments when expressed ectopically and impaired host protein secretion. 31,39 Genetic studies have found a redundancy of function among effector candidates, consistent with the failure to identify effectors by using early genetic screens. Although several factors are now identified, the list is far from complete, and the mechanism by which replication is enhanced and lysosomal fusion is prevented remains undefined.…”
Section: Identification Of T4ss-secreted Substratesmentioning
confidence: 85%
See 1 more Smart Citation
“…Candidate effectors were shown to target secretory pathway compartments when expressed ectopically and impaired host protein secretion. 31,39 Genetic studies have found a redundancy of function among effector candidates, consistent with the failure to identify effectors by using early genetic screens. Although several factors are now identified, the list is far from complete, and the mechanism by which replication is enhanced and lysosomal fusion is prevented remains undefined.…”
Section: Identification Of T4ss-secreted Substratesmentioning
confidence: 85%
“…Although shown to be required to prevent trafficking to the lysosome, the mechanistic steps involved, including interacting partners, enzymatic reactions, protein modifications, and detailed intracellular trafficking, are only now being described after a series of experiments in which Brucella gene reporter fusions were found to be secreted in a T4SS-dependent manner. 23,25,39 Putative effector candidates were identified in silico on the basis of several criteria, including shared features with effectors expressed by other bacteria, eukaryotic motifs, GC content, and limited distribution across bacterial genera. Candidate effectors were shown to target secretory pathway compartments when expressed ectopically and impaired host protein secretion.…”
Section: Identification Of T4ss-secreted Substratesmentioning
confidence: 99%
“…To date, 15 T4SS substrates have been identified (4 -8, 28), but we do not know the molecular mechanism that mediates their secretion and/or translocation. Interestingly, some of these effectors, like SepA, Bpe123, Bpe275, Bpe043, VceC, BspC, BspE, and BspB, either have a predicted periplasmic signal peptide or a transmembrane domain (5)(6)(7)(8), which highlights the complexity of the secretion process.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that this new effector protein is secreted in a VirB-dependent manner, that its inactivation affects the intracellular trafficking particularly during the initial stages, and that its secretion involves a periplasmic intermediate (6). Although in Brucella this was the first report identifying a VirB substrate with a twostep secretion process involving a periplasmic intermediate, it was reported that other effectors have a predicted periplasmic signal peptide or putative transmembrane domains (5,7,8). We report here the identification in Brucella of a homologue of the A. tumefaciens virJ gene and characterized this gene genetically and biochemically.…”
mentioning
confidence: 89%
See 1 more Smart Citation